Canadian non-tariff barriers to trade - Stegemann, Klaus; Canadian Economic Policy Committee (Montreal, Private Planning Association of Canada, 1973)
This book reviews and analyses five of the six major NTBs selected by an international research team for intensive investigation in terms of their respective countries' laws and practices.
"Sponsored by The Canadian Economic Policy Committee, Private Planning Association of Canada."
Includes bibliographical references.
osc 19/07/2018
Loans
Keywords: Trade; Canada